(untitled) (Evidence-Based Pharmacotherapy in Clinical Practice, 2025)
Author Miss Sri Ramyavathi Seelam PharmD Intern, Department of Pharmacy Practice, Koringa College of Pharmacy, Korangi, Andhra Pradesh, India Abstract Pharmacological management of renal conditions requires precise medication selection and dosing based on kidney function parameters. Acute kidney injury protocols incorporate preventive strategies, supportive measures, and specific interventions based on underlying etiology and severity markers. Chronic kidney disease management utilizes multiple drug classes targeting complications including anemia, mineral disorders, and cardiovascular risk with systematic monitoring of disease progression. Electrolyte disorder treatment requires careful assessment of underlying mechanisms with targeted replacement or elimination strategies based on severity and chronicity. Drug dosing protocols in renal dysfunction incorporate pharmacokinetic principles with systematic adjustment based on estimated glomerular filtration rate and specific drug properties. Dialysis considerations include medication removal characteristics, timing of administration, and supplemental dosing requirements. Treatment strategies emphasize prevention of further kidney damage while managing multiple comorbid conditions Keywords: Renal pharmacotherapy, Kidney injury, Electrolyte disorders, Drug dosing, Dialysis VIEW PDF